THE RELATIONSHIP BETWEEN IRON INHIBITORS AND SLEEP QUALITY WITH HEMOGLOBIN LEVELS IN ADOLESCENT GIRLS - Delia Nurul Fitriana; Noerfitri Noerfitri (PRIMA WIYATA HEALTH, 2026)
Background: Adolescents are at greater risk of anemia. One indicator of anemia is hemoglobin. Frequent consumption of iron inhibitors can inhibit iron absorption, thereby lowering hemoglobin levels. Furthermore, adolescents with poor sleep quality are 2.9 times more likely to experience low hemoglobin levels. The negative impact of low hemoglobin levels can lead to decreased concentration and academic achievement, ultimately impacting the quality of human resources in the long term. Objective: This study aims to analyze the relationship between the frequency of iron inhibitor consumption and sleep quality on hemoglobin levels in female adolescents at SMAN 6 Bekasi. Methods: This study is a quantitative study with a cross-sectional design. The sample size was 100 female students of SMAN 6 Bekasi, selected by the consecutive sampling method. Data were collected using questionnaires, namely the Food Frequency Questionnaire and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Validity and reliability tests have been conducted on the PSQI questionnaire, with the results of 19 valid and reliable questions. This device measures the hemoglobin level in a blood sample using a brief electrical potential change generated by the chemical interaction between the electrode and the strip. Results: The results of the analysis using Chi-square showed a p-value on the variable frequency of consumption of iron inhibitors > 0.05 and variable sleep quality < 0.05 with OR 2.923 (95% CI OR: 1.245-6.865). Conclusion: Most respondents consumed iron inhibitor sources, but the frequency of consumption was not related to hemoglobin levels, while sleep quality showed a significant relationship with hemoglobin levels.